2021
DOI: 10.1177/23821205211037756
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and Initial Participant Feedback of an Online Anatomy and Radiology Contouring Bootcamp in Radiation Oncology

Abstract: BACKGROUND The Anatomy and Radiology Contouring (ARC) Bootcamp was a face-to-face (F2F) course designed to ensure radiation oncology residents were equipped with the knowledge and skillset to use radiation therapy techniques properly. The ARC Bootcamp was proven to be a useful educational intervention for improving learners’ knowledge of anatomy and radiology and contouring ability. An online version of the course was created to increase accessibility to the ARC Bootcamp and provide a flexible, self-paced lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Penelitian ini merupakan Research and Development dengan menggunakan model ADDIE (Analyze, Design, Development, Implementation, Evaluation) (Branch, 2010;Eansor et al, 2021). Model ini dipilih oleh peneliti untuk mengembangkan produk bahan ajar yang efektif karena memfasilitasi konstruksi pengetahuan dan keterampilan peserta didik dalam rencana pembelajaran terbimbing yang bersifat instruksional (Branch, 2010).…”
Section: Metodeunclassified
“…Penelitian ini merupakan Research and Development dengan menggunakan model ADDIE (Analyze, Design, Development, Implementation, Evaluation) (Branch, 2010;Eansor et al, 2021). Model ini dipilih oleh peneliti untuk mengembangkan produk bahan ajar yang efektif karena memfasilitasi konstruksi pengetahuan dan keterampilan peserta didik dalam rencana pembelajaran terbimbing yang bersifat instruksional (Branch, 2010).…”
Section: Metodeunclassified
“…Preliminary work carried out in Germany and other countries has identified and later concluded that the synergistic collaboration of multiple disciplines in the case-based teaching of radiation oncology is very important for the successful education of future residents [ 25 27 ]. Additionally, a study from Canada shows that case-based learning in anatomy and radiology contouring is an ideal candidate for transfer to online formats, and course participants particularly appreciate the flexible, self-paced learning environment [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of other medical specialties have shown that online teaching formats are challenging due to lower completion rates but can, however, offer a very effective learning experience and other benefits such as geographic flexibility [ 28 – 30 ]. Within radiation oncology, online courses in the field have shown high effectiveness in delivering knowledge to both residents and students [ 2 , 14 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%